Lower Serum Level of Anti-tetanus Toxin Antibodies in Patients with Type 2 Diabetes Mellitus - M. Nemati; M. Zarrin; S.A. Mir-Abdollahi; M.T. Rezayati; V. Mirzaee; A. Bagheri; M. Ebrahimi; A. Jafarzadeh (Acta Medica Indonesiana)
Aim: to evaluate the serum levels of anti-tetanus toxin antibodies (anti-TTA) in patients with type 2 diabetes mellitus (DM) and in a control group. Methods: totally, 100 patients with type 2 DM and 100 age-and sex-matched healthy individuals were enrolled to study. The presence of type 2 DM confirmed according to the clinical and para-clinical criteria such as fasting plasma glucose above 126 mg/dl. A peripheral blood sample was collected from all subjects. The serum samples of participants tested for the levels of anti-TTA by ELISA method. The serum antitoxin concentration ≥0.1 IU/mL was considered as a protective level of antibody. Results: the seroprotective rate in healthy group was significantly higher than diabetic group (99% vs. 92%; p<0.02). The mean titer of anti-TTA in healthy group (5.32±0.26 IU/ml) was also significantly higher than diabetic patients (3.46±0.26 IU/ml; p<0.001). In diabetic men the mean titer of anti-TTA was significantly higher in comparison to diabetic women (3.94±0.34 IU/ml vs 2.59±0.36 IU/ml; p<0.01). In diabetic patients the seroprotective rate and the mean titer of anti-TTA in subjects with age >40 years was also lower in comparison to those with age <40 years (89.23% vs 97.14%; p<0.15 and 4.57±0.38 IU/ml vs 2.86±0.32 IU/ml; P<0.002, respectively). The mean titer of anti-TTA was significantly higher in patients with diabetes duration <5 years in comparison to patients with disease duration >5 years (3.91±0.35 IU/ml vs 2.85±0.38 IU/ml; p<0.04). Conclusion: these results showed lower levels of anti-TTA in patients with type 2 DM, in diabetic women, in patients aged >40 years and in diabetic patients with disease duration >5 years .